Identifying different typologies of experiences and coping strategies in men with rheumatoid arthritis: a Q-methodology study. Issue 10 (3rd October 2016) - Flurey, Caroline A; Hewlett, Sarah; Rodham, Karen; White, Alan; Noddings, Robert; Kirwan, John R
Abstract : Objective: To identify typologies of experiences and coping strategies of men with rheumatoid arthritis (RA). Design: Q-methodology (a qualitative and quantitative approach to grouping people according to their subjective opinion). Men with RA sorted 64 statements relating to their experience of living with RA according to level of agreement across a normal distribution grid. Data were examined using Q-factor analysis. Setting: Rheumatology outpatient departments in the UK. Participants: 30 of 65 invited men with RA participated in this study (46%). Results: All participants ranked highly the need to be well informed about their medication and the importance of keeping a positive attitude. 2 factors describing the experiences and coping strategies of male patients living with RA were identified: factor A: 'acknowledge, accept and adapt' (n=14) take a proactive approach to managing the impact of RA and find different ways of doing things; while factor B: 'trying to match up to a macho ideal' (n=8) are determined to continue with their pre-RA lives, and therefore push themselves to carry on even if this causes them pain. They are frustrated and angry due to the impact of RA but they internalise this rather than directing it at others. Conclusions: While some men adapt to their RA by renegotiating their masculine identity, others struggle to relinquish their traditional masculine roles. Further research is needed to identify whether the finding that there are 2 distinct groups of men with RA can be generalised, and if so whether the differences can be explained by clinical, social or psychological factors, which may inform different therapeutic approaches.